Análise da temperatura de superfície em ambientes urbanos: um estudo por meio do sensoriamento remoto na cidade de Porto Velho/RO (1985-2011) - Graziela Tosini Tejas; Dorisvalder Dias Nunes; Reginaldo Martins da Silva de Souza; Ana Cristina Strava Corrêa; Michel Watanabe (Confins)
The urban climate is a phenomenon resulting from the urban site, once the changes in use and occupation of land interfere in its climate, promoting the so-called heat islands. In this sense, the present work, aims to study Porto Velho city urban area, capital of Rondonia, in order to analyze the spatial distribution of land surface temperature and vegetation density through 1985 to 2011 period, using data of the TM from series Landsat sensor -5, processed in SPRING software version 5.1.8, developed by the National Institute for Space Research (INPE). The method used was based on the urban climate theory, developed by Monteiro (1976) from the understanding of the climate urban environment parts interpretation: manufacturing and production. A reduction of vegetation cover was deduced from the vegetation index (NDVI) which expanded from the central area, in 1985, to other parts of the city limits in 2011. The removal of the vegetation due to the disorderly urbanization process common at the Western Amazon, favored the increase in surface temperature, promoting diffuse heat islands throughout the study area, known as "heat islands". Therefore, it was found that the removal of vegetation caused up to 10o degrees on the increase of surface temperature between 1995 and 2011, and appears as one of the major factor of regional and local climate change.